Printing adhesive as well as preparation method and application thereof

By combining RAFT polymerization and fine emulsion polymerization technology, a high silicone content polyacrylate emulsion is prepared as a printing adhesive, which solves the problems of insufficient color of the paint printing, hard feel and low color fastness, and achieves deeper and brighter color and better performance.

CN119390909APending Publication Date: 2025-02-07HANGZHOU TRANSFAR FINE CHEM CO LTD +2
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411319378.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-19
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The color of the paint printing is not dark enough, not bright enough, the feel is hard, and the color fastness is low, so it cannot be compared with the active printing.

Method used

The mixture of amphiphilic RAFT emulsifier, the mixture of aldehyde-free crosslinking monomer and water, acrylate, styrene, acrylonitrile, hydroxyacrylate, vinyl silicone oil and zinc oxide, pre-emulsification and ultrasonic dispersion, combined with reversible addition - Break chain transfer (RAFT) polymerization and fine emulsion polymerization technology to prepare random polyacrylate emulsions with high silicone content as printing adhesives.

Benefits of technology

It improves the color depth and brightness of printed fabrics, enhances color fastness and softness of the hand, and overcomes the insufficient performance of traditional paint printing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005053590090000021
    Figure BDA0005053590090000021
  • Figure BDA0005053590090000061
    Figure BDA0005053590090000061
  • Figure BDA0005053590090000091
    Figure BDA0005053590090000091
Patent Text Reader

Abstract

The invention relates to a printing adhesive as well as a preparation method and application thereof. The preparation method comprises the following steps: mixing an amphiphilic RAFT emulsifier, a formaldehyde-free crosslinking monomer and water to prepare a water phase, wherein the molecular weight of the amphiphilic RAFT emulsifier is 1000-5000; mixing acrylate, styrene, acrylonitrile, hydroxyl acrylate, vinyl silicone oil and zinc oxide to prepare an oil phase, wherein the mass fraction of the vinyl silicone oil in the oil phase is 10-30%; mixing the water phase and the oil phase, pre-emulsifying, and performing ultrasonic dispersion to obtain an emulsion; and reacting the emulsion with part of the initiator in a protective atmosphere at the temperature of 60-80 DEG C, then adding an aqueous solution of alkali in batches for heat preservation, finally adding the rest of the initiator for continuous reaction, and after the reaction is finished, adding a blocked isocyanate cross-linking agent for mixing to obtain the printing adhesive. When the printing adhesive prepared by the preparation method disclosed by the invention is used for pigment printing, a printed fabric can be dark and bright in color and has good color fastness and hand feeling.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of textile printing and dyeing, in particular to a printing adhesive and a preparation method and application thereof. Background Art

[0002] Pigment printing is a printing process that uses water-based adhesives to adhere paint particles to the surface of fabrics. It has the advantages of simple operation process and equipment, complete color spectrum, and clear printing patterns. It is widely used in printing various fibers and blended fabrics. In addition, compared with the reactive printing process, pigment printing has outstanding environmental protection characteristics. After printing, it only needs one high-temperature setting, without steaming and washing, avoiding the pollution of printing and dyeing wastewater to the environment. At the same time, it shortens the process flow, saves water, electricity, and gas, and reduces CO2 emissions. Therefore, it is widely used in the printing and dyeing industry.

[0003] However, the color of the pigment printing is not deep enough and not bright enough, the film formation of the adhesive in the printing paste will make the fabric feel hard, and the adhesive has limited fixation ability on the paint particles, which reduces the friction color fastness, which makes the performance of the pigment printing inferior to that of the reactive printing. Although the polyacrylate emulsion disclosed in patent CN114163590B has good hydrophobic and oleophobic properties, when it is used in pigment printing, the printing color fastness is poor and the hand feel is hard, and due to its core-shell structure, the transparency of the adhesive film decreases, which reduces the color depth and brightness of the printed fabric. Summary of the invention

[0004] Based on this, it is necessary to provide a printing adhesive and its preparation method and application to address the above problems; the printing adhesive prepared by the preparation method of the present invention can be used for paint printing to make the color of the printed fabric deep and bright, and have good color fastness and feel.

[0005] A method for preparing a printing adhesive comprises the following steps:

[0006] Mixing an amphiphilic RAFT emulsifier, an aldehyde-free crosslinking monomer and water to prepare an aqueous phase, wherein the amphiphilic RAFT emulsifier has a molecular weight of 1000-5000;

[0007] The oil phase is prepared by mixing acrylate, styrene, acrylonitrile, hydroxy acrylate, vinyl silicone oil and zinc oxide, wherein the mass fraction of the vinyl silicone oil in the oil phase is 10%-30%;

[0008] The water phase and the oil phase are mixed for pre-emulsification, and then ultrasonically dispersed to obtain an emulsion;

[0009] Under protective atmosphere and temperature conditions of 60°C-80°C, the emulsion is first reacted with part of the initiator, then an aqueous solution of alkali is added in batches for heat preservation, and finally the remaining initiator is added to continue the reaction. After the reaction is completed, a blocked isocyanate crosslinking agent is added and mixed to obtain a printing adhesive.

[0010] In one embodiment, the general structural formula of the amphiphilic RAFT emulsifier is as shown in formula (1),

[0011]

[0012] Among them, -R1 is selected from ethylmercapto, isopropylmercapto, butylmercapto or C12mercapto, -R2- is selected from the structural unit of styrene, the structural unit of acrylate, the structural unit of methacrylate or the structural unit of acrylonitrile, -R3- is selected from the structural unit of hydroxyethyl acrylate, the structural unit of hydroxyethyl methacrylate, the structural unit of hydroxypropyl acrylate or the structural unit of hydroxymethyl acrylamide, -R4- is selected from the structural unit of acrylic acid or the structural unit of methacrylic acid, -R5 is selected from isopropanoic acid, 2-diisobutyric acid, 2-isobutyronitrile, cyanopentanoic acid or 3-benzoic acid, the ratio of x to y is 1:2-1:9, and the ratio of the sum of x, y to n is 2:1-5:1.

[0013] In one embodiment, the amount of the amphiphilic RAFT emulsifier is 0.1%-6% of the sum of the mass of the formaldehyde-free crosslinking monomer, acrylate, styrene, acrylonitrile, hydroxy acrylate and vinyl silicone oil.

[0014] In one embodiment, the oil phase includes 20-30 parts by weight of acrylate, 3-8 parts by weight of styrene, 3-8 parts by weight of acrylonitrile, 1-3 parts by weight of hydroxy acrylate, 2-10 parts by weight of vinyl silicone oil and 0.1-0.5 parts by weight of zinc oxide.

[0015] In one embodiment, the aldehyde-free cross-linking monomer is selected from at least one of N-n-butoxymethyl acrylamide and N-(isobutoxymethyl) acrylamide;

[0016] And / or, the acrylate is at least one selected from methyl acrylate, ethyl acrylate, butyl acrylate or isooctyl acrylate;

[0017] And / or, the hydroxy acrylate is at least one selected from hydroxyethyl acrylate, hydroxypropyl acrylate, hydroxyethyl methacrylate or hydroxypropyl methacrylate;

[0018] And / or, the vinyl silicone oil is selected from vinyl-terminated polydimethylsiloxane and vinyl-terminated polymethylvinylsiloxane, and the viscosity of the vinyl silicone oil is 300 mPa·s-2000 mPa·s.

[0019] In one of the embodiments, in the emulsion, the mass ratio of the aldehyde-free cross-linking monomer to the acrylate is 1:4-1:30.

[0020] In one embodiment, the mass ratio of the partial initiator to the remaining initiator is 4:1-6:1;

[0021] And / or, the total time of adding the aqueous solution of the alkali in batches is 10 min-15 min;

[0022] And / or, the total amount of the initiator added is 0.05%-0.5% of the sum of the mass of the aldehyde-free crosslinking monomer, acrylate, styrene, acrylonitrile, hydroxy acrylate and vinyl silicone oil;

[0023] And / or, the amount of the aqueous solution of alkali is 0.5%-6% of the sum of the mass of the aldehyde-free cross-linking monomer, acrylate, styrene, acrylonitrile, hydroxy acrylate and vinyl silicone oil;

[0024] And / or, the amount of the blocked isocyanate crosslinking agent is 5%-15% of the sum of the mass of the formaldehyde-free crosslinking monomer, acrylate, styrene, acrylonitrile, hydroxy acrylate and vinyl silicone oil;

[0025] And / or, the emulsion reacts with part of the initiator for 15 min-30 min, the aqueous solution of alkali is kept warm for 1.5 h-2 h, and the remaining initiator is added for 0.5 h-1 h.

[0026] In one embodiment, the initiator is selected from at least one of ammonium persulfate, potassium persulfate or sodium bisulfite;

[0027] And / or, the aqueous solution of alkali is at least one selected from an aqueous solution of potassium hydroxide, an aqueous solution of sodium hydroxide, and aqueous ammonia;

[0028] And / or, the blocked isocyanate cross-linking agent is selected from at least one of bisulfite compound blocked polyisocyanate, alcohol compound blocked polyisocyanate or phenol compound blocked polyisocyanate.

[0029] A printing adhesive prepared by the above-mentioned preparation method of the printing adhesive, wherein the printing adhesive contains 2%-10% of organic silicon.

[0030] A printing adhesive as described above is used for pigment printing.

[0031] The preparation method of the present invention combines reversible addition-fragmentation chain transfer (RAFT) polymerization and mini-emulsion polymerization technology to prepare a random polyacrylate emulsion with a high silicone content. As a printing adhesive, compared with the prior art, it has the following advantages: (1) mini-emulsion polymerization can improve the polymerization stability of silicone monomers, and by utilizing the advantage of RAFT polymerization technology for a wider range of monomer applications, the amount of silicone monomers in the emulsion system and the monomer conversion rate can be further increased, and the refractive index of the adhesive film can be lowered, thereby improving the coloring depth of the paint printing; (2) the random structure of the RAFT emulsion The film formed by the emulsion has high transparency. At the same time, since the RAFT emulsion system does not contain a surfactant, the transparency of the film is further improved, which is beneficial to improving the coloring depth of the paint printing; (3) The present invention adopts an intermittent polymerization method, the preparation method is simple and efficient, and by adding zinc oxide and an alkaline solution to reduce the polymerization heating rate and improve the emulsification ability of RAFT, thereby significantly improving the stability of the polymerization reaction; (4) The hydroxyl groups that have a strong interaction with the substrate are introduced and enriched on the surface of the latex, which has a synergistic effect with the blocked isocyanate cross-linking agent, thereby improving the color fastness of the printing. DETAILED DESCRIPTION

[0032] For ease of understanding of the present invention, the present invention will be described in more detail below. However, it should be understood that the present invention can be implemented in many different forms and is not limited to the embodiments or examples described herein. On the contrary, the purpose of providing these embodiments or examples is to make the understanding of the disclosure of the present invention more thorough and comprehensive.

[0033] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific implementation methods or embodiments, and are not intended to limit the present invention. The optional scope of the term "and / or" used herein includes any one of two or more related listed items, and also includes any and all combinations of related listed items, and the combinations include any two related listed items, any more related listed items, or all related listed items.

[0034] In the conventional emulsion polymerization process, the organosiloxane monomer needs to migrate from the monomer droplets to the latex particles through the water phase, and it is difficult to avoid contact with the water phase to hydrolyze and condense into coagulants, which leads to instability and slagging of the emulsion polymerization. Mini-emulsion polymerization is mainly based on the nucleation of monomer droplets, so that the monomer droplets directly capture the free radicals in the water for polymerization. Although it can effectively slow down the premature hydrolysis of the organosiloxane monomer, for free radical polymerization, the reactivity rate of the organosiloxane monomer is quite different from that of the acrylate monomer, and it is not easy to copolymerize with the acrylate monomer, resulting in a significant decrease in the conversion rate of the organosiloxane monomer with the increase of the monomer dosage.

[0035] Based on this, the present invention provides a method for preparing a printing adhesive, comprising the following steps:

[0036] S1, mixing an amphiphilic RAFT emulsifier, an aldehyde-free crosslinking monomer and water to prepare an aqueous phase, wherein the amphiphilic RAFT emulsifier has a molecular weight of 1000-5000;

[0037] S2, mixing acrylate, styrene, acrylonitrile, hydroxy acrylate, vinyl silicone oil and zinc oxide to prepare an oil phase, wherein the mass fraction of the vinyl silicone oil in the oil phase is 10%-30%;

[0038] S3, mixing the water phase and the oil phase for pre-emulsification, and then performing ultrasonic dispersion to obtain an emulsion;

[0039] S4, under protective atmosphere and temperature conditions of 60°C-80°C, the emulsion is first reacted with part of the initiator, then an aqueous solution of alkali is added in batches for heat preservation, and finally the remaining initiator is added to continue the reaction, and after the reaction is completed, a blocked isocyanate cross-linking agent is added and mixed to obtain a printing adhesive.

[0040] The preparation method of the present invention combines reversible addition-fragmentation chain transfer (RAFT) polymerization and mini-emulsion polymerization technology to prepare a random polyacrylate emulsion with a high silicone content. As a printing adhesive, compared with the prior art, it has the following advantages: (1) mini-emulsion polymerization can improve the polymerization stability of silicone monomers, and by utilizing the advantage of RAFT polymerization technology for a wider range of monomer applications, the amount of silicone monomers in the emulsion system and the monomer conversion rate can be further increased, and the refractive index of the adhesive film can be lowered, thereby improving the coloring depth of the paint printing; (2) the random structure of the RAFT emulsion The film formed by the emulsion has high transparency. At the same time, since the RAFT emulsion system does not contain a surfactant, the transparency of the film is further improved, which is beneficial to improving the coloring depth of the paint printing; (3) The present invention adopts an intermittent polymerization method, the preparation method is simple and efficient, and by adding zinc oxide and an alkaline solution to reduce the polymerization heating rate and improve the emulsification ability of RAFT, thereby significantly improving the stability of the polymerization reaction; (4) The hydroxyl groups that have a strong interaction with the substrate are introduced and enriched on the surface of the latex, which has a synergistic effect with the blocked isocyanate cross-linking agent, thereby improving the color fastness of the printing.

[0041] In step S1, the general structural formula of the amphiphilic RAFT emulsifier is shown in formula (1):

[0042]

[0043] Among them, -R1 is selected from ethylmercapto, isopropylmercapto, butylmercapto or C12mercapto, -R2- is selected from the structural unit of styrene, the structural unit of acrylate, the structural unit of methacrylate or the structural unit of acrylonitrile, -R3- is selected from the structural unit of hydroxyethyl acrylate, the structural unit of hydroxyethyl methacrylate, the structural unit of hydroxypropyl acrylate or the structural unit of hydroxymethyl acrylamide, -R4- is selected from the structural unit of acrylic acid or the structural unit of methacrylic acid, -R5 is selected from isopropanoic acid, 2-diisobutyric acid, 2-isobutyronitrile, cyanopentanoic acid or 3-benzoic acid, the ratio of x to y is 1:2-1:9, and the ratio of the sum of x, y to n is 2:1-5:1.

[0044] In one embodiment, the amount of the amphiphilic RAFT emulsifier is 0.1%-6%, preferably 3%-5%, of the sum of the mass of the aldehyde-free crosslinking monomer, acrylate, styrene, acrylonitrile, hydroxy acrylate and vinyl silicone oil.

[0045] Wherein, the aldehyde-free cross-linking monomer is selected from at least one of N-n-butoxymethyl acrylamide and N-(isobutoxymethyl) acrylamide.

[0046] In step S2, the oil phase includes 20-30 parts by weight of acrylate, 3-8 parts by weight of styrene, 3-8 parts by weight of acrylonitrile, 1-3 parts by weight of hydroxy acrylate, 2-10 parts by weight of vinyl silicone oil and 0.1-0.5 parts by weight of zinc oxide.

[0047] Preferably, the mass fraction of the vinyl silicone oil in the oil phase is 10%-27%.

[0048] Preferably, in the emulsion, the mass ratio of the aldehyde-free cross-linking monomer to the acrylate is 1:4-1:30.

[0049] Specifically, the acrylic acid ester is selected from at least one of methyl acrylate, ethyl acrylate, butyl acrylate or isooctyl acrylate, preferably ethyl acrylate.

[0050] The hydroxy acrylate is selected from at least one of hydroxyethyl acrylate, hydroxypropyl acrylate, hydroxyethyl methacrylate or hydroxypropyl methacrylate.

[0051] The vinyl silicone oil is selected from vinyl-terminated polydimethylsiloxane and vinyl-terminated polymethylvinylsiloxane, and the viscosity of the vinyl silicone oil is 300mPa·s-2000mPa·s, preferably 500mPa·s-1000mPa·s.

[0052] The zinc oxide is preferably nano zinc oxide powder.

[0053] It is understandable that the present invention does not limit the preparation order of step S1 and step S2. Step S1 can be prepared first, and then step S2, or step S2 can be prepared first, and then step S1, or step S1 and step S2 can be prepared simultaneously.

[0054] In step S3, the pre-emulsification method is preferably high-speed shear emulsification. It is understandable that an ice bath can be used for cooling during the ultrasonic dispersion process.

[0055] In step S4, before the emulsion reacts with part of the initiator, a protective gas is preferably introduced first, and the protective gas includes but is not limited to nitrogen.

[0056] Preferably, the total amount of the initiator added is 0.05%-0.5% of the sum of the mass of the formaldehyde-free crosslinking monomer, acrylate, styrene, acrylonitrile, hydroxy acrylate and vinyl silicone oil.

[0057] Preferably, the amount of the aqueous solution of alkali is 0.5%-6% of the sum of the mass of the formaldehyde-free cross-linking monomer, acrylate, styrene, acrylonitrile, hydroxy acrylate and vinyl silicone oil.

[0058] Preferably, the amount of the blocked isocyanate crosslinking agent is 5%-15% of the sum of the mass of the formaldehyde-free crosslinking monomer, acrylate, styrene, acrylonitrile, hydroxy acrylate and vinyl silicone oil.

[0059] Preferably, the mass of part of the initiator is greater than the mass of the remaining initiator, and more preferably, the mass ratio of part of the initiator to the remaining initiator is 4:1-6:1.

[0060] Preferably, the reaction time of the emulsion and part of the initiator is 15min-30min; the total time of adding the aqueous alkali solution in batches is 10min-15min, and the batch addition method is preferably dropwise addition; the insulation time of the aqueous alkali solution is 1.5h-2h; the reaction time of adding the remaining initiator is 0.5h-1h.

[0061] Specifically, the initiator is selected from at least one of ammonium persulfate, potassium persulfate or sodium bisulfite.

[0062] The aqueous alkali solution is selected from at least one of an aqueous potassium hydroxide solution, an aqueous sodium hydroxide solution, and aqueous ammonia.

[0063] The blocked isocyanate cross-linking agent is selected from at least one of bisulfite compound blocked polyisocyanate, alcohol compound blocked polyisocyanate or phenol compound blocked polyisocyanate, preferably bisulfite compound blocked polyisocyanate.

[0064] The present invention also provides a printing adhesive prepared by the preparation method of the printing adhesive as described above and its application, wherein the printing adhesive contains 2%-10% of silicone, more preferably 6%-8% of silicone, and the printing adhesive is used for paint printing, thereby overcoming the problems of traditional paint printing such as insufficient color depth and brightness, poor hand feel, and low color fastness.

[0065] The printing adhesive and its preparation method and application are further described below by the following specific examples. However, those skilled in the art will understand that the following examples are only used to illustrate the present invention and should not be considered to limit the scope of the present invention. If no specific conditions are specified in the examples, the conventional conditions or the conditions recommended by the manufacturer are followed. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be obtained commercially.

[0066] Example 1

[0067]

[0068] 245 g of deionized water, 10 g of an amphiphilic RAFT emulsifier represented by formula (1-1) and 8 g of N-n-butoxymethyl acrylamide were added to a reactor and stirred to form a water phase.

[0069] 108 g of butyl acrylate, 18 g of styrene, 18 g of acrylonitrile, 6 g of hydroxyethyl acrylate, 35 g of vinyl silicone oil (V401-310) and 1 g of nano zinc oxide were added into a beaker and stirred evenly to prepare the oil phase.

[0070] Under the action of a high-speed shear emulsifier, the oil phase is slowly added to the water phase for pre-emulsification, and then ultrasonic dispersion is performed using an ultrasonic cell crusher, during which an ice bath is used for cooling to obtain an emulsion.

[0071] Dissolve 0.5g of ammonium persulfate and 0.5g of sodium bisulfite in 20g of deionized water respectively as initiators. Transfer the ultrasonically dispersed emulsion to a four-necked flask, pass nitrogen for 15 minutes, heat to 65°C, and add 5 / 6 of ammonium persulfate and sodium bisulfite aqueous solutions in sequence to initiate the reaction. After the temperature stabilizes at 80°C, slowly add 5g of ammonia water, control the addition for 15 minutes, and then keep warm for 2 hours. After the insulation is completed, add the remaining 1 / 6 of the ammonium persulfate and sodium bisulfite aqueous solutions and continue the reaction for 0.5 hours. After the reaction is completed, cool to room temperature, add 25g of bisulfite compound to block the isocyanate crosslinker, stir evenly, filter the material, and obtain a printing adhesive with a silicone content of 7%.

[0072] Example 2

[0073] 245 g of deionized water, 10 g of an amphiphilic RAFT emulsifier represented by formula (1-1) and 8 g of N-n-butoxymethyl acrylamide were added to a reactor and stirred to form a water phase.

[0074] 108 g of butyl acrylate, 18 g of styrene, 18 g of acrylonitrile, 6 g of hydroxyethyl acrylate, 35 g of vinyl silicone oil (V401-1000) and 1 g of nano zinc oxide were added into a beaker and stirred evenly to prepare the oil phase.

[0075] Under the action of a high-speed shear emulsifier, the oil phase is slowly added to the water phase for pre-emulsification, and then ultrasonic dispersion is performed using an ultrasonic cell crusher, during which an ice bath is used for cooling to obtain an emulsion.

[0076] Dissolve 0.5g of ammonium persulfate and 0.5g of sodium bisulfite in 20g of deionized water respectively as initiators. Transfer the ultrasonically dispersed emulsion to a four-necked flask, pass nitrogen for 15 minutes, heat to 65°C, and add 5 / 6 of ammonium persulfate and sodium bisulfite aqueous solutions in sequence to initiate the reaction. After the temperature stabilizes at 80°C, slowly add 5g of ammonia water, control the addition for 15 minutes, and then keep warm for 2 hours. After the insulation is completed, add the remaining 1 / 6 of the ammonium persulfate and sodium bisulfite aqueous solutions and continue the reaction for 0.5 hours. After the reaction is completed, cool to room temperature, add 25g of bisulfite compound to block the isocyanate crosslinker, stir evenly, filter the material, and obtain a printing adhesive with a silicone content of 7%.

[0077] Example 3

[0078] 245 g of deionized water, 10 g of an amphiphilic RAFT emulsifier represented by formula (1-1) and 8 g of N-n-butoxymethyl acrylamide were added to a reactor and stirred to form a water phase.

[0079] 108 g of butyl acrylate, 18 g of styrene, 18 g of acrylonitrile, 6 g of hydroxyethyl acrylate, 35 g of vinyl silicone oil (V401-2000) and 1 g of nano zinc oxide were added into a beaker and stirred evenly to prepare the oil phase.

[0080] Under the action of a high-speed shear emulsifier, the oil phase is slowly added to the water phase for pre-emulsification, and then ultrasonic dispersion is performed using an ultrasonic cell crusher, during which an ice bath is used for cooling to obtain an emulsion.

[0081] Dissolve 0.5g of ammonium persulfate and 0.5g of sodium bisulfite in 20g of deionized water respectively as initiators. Transfer the ultrasonically dispersed emulsion to a four-necked flask, pass nitrogen for 15 minutes, heat to 65°C, and add 5 / 6 of ammonium persulfate and sodium bisulfite aqueous solutions in sequence to initiate the reaction. After the temperature stabilizes at 80°C, slowly add 5g of ammonia water, control the addition for 15 minutes, and then keep warm for 2 hours. After the insulation is completed, add the remaining 1 / 6 of the ammonium persulfate and sodium bisulfite aqueous solutions and continue the reaction for 0.5 hours. After the reaction is completed, cool to room temperature, add 25g of bisulfite compound to block the isocyanate crosslinker, stir evenly, filter the material, and obtain a printing adhesive with a silicone content of 7%.

[0082] Example 4

[0083] 244 g of deionized water, 10 g of an amphiphilic RAFT emulsifier represented by formula (1-1) and 8 g of N-n-butoxymethyl acrylamide were added to a reactor and stirred to form a water phase.

[0084] 120 g of butyl acrylate, 20 g of styrene, 20 g of acrylonitrile, 6 g of hydroxyethyl acrylate, 20 g of vinyl silicone oil (V401-1000) and 1 g of nano zinc oxide were added into a beaker and stirred evenly to prepare the oil phase.

[0085] Under the action of a high-speed shear emulsifier, the oil phase is slowly added to the water phase for pre-emulsification, and then ultrasonic dispersion is performed using an ultrasonic cell crusher, during which an ice bath is used for cooling to obtain an emulsion.

[0086] Dissolve 0.5g of ammonium persulfate and 0.5g of sodium bisulfite in 20g of deionized water respectively as initiators. Transfer the ultrasonically dispersed emulsion to a four-necked flask, pass nitrogen for 15 minutes, heat to 65°C, and add 5 / 6 of the aqueous solution of ammonium persulfate and sodium bisulfite in turn to initiate the reaction. After the temperature stabilizes at 80°C, slowly add 5g of ammonia water, control the addition for 15 minutes, and then keep warm for 2 hours. After the insulation is completed, add the remaining 1 / 6 of the aqueous solution of ammonium persulfate and sodium bisulfite, and continue the reaction for 0.5 hours. After the reaction is completed, cool to room temperature, add 25g of bisulfite compound to block the isocyanate crosslinker, stir evenly, filter the material, and obtain a printing adhesive with a silicone content of 4%.

[0087] Example 5

[0088] 246 g of deionized water, 10 g of an amphiphilic RAFT emulsifier represented by formula (1-1) and 8 g of N-n-butoxymethyl acrylamide were added to a reactor and stirred to form a water phase.

[0089] 100 g of butyl acrylate, 14 g of styrene, 14 g of acrylonitrile, 6 g of hydroxyethyl acrylate, 50 g of vinyl silicone oil (V401-1000) and 1 g of nano zinc oxide were added into a beaker and stirred evenly to prepare the oil phase.

[0090] Under the action of a high-speed shear emulsifier, the oil phase is slowly added to the water phase for pre-emulsification, and then ultrasonic dispersion is performed using an ultrasonic cell crusher, during which an ice bath is used for cooling to obtain an emulsion.

[0091] Dissolve 0.5g of ammonium persulfate and 0.5g of sodium bisulfite in 20g of deionized water respectively as initiators. Transfer the ultrasonically dispersed emulsion to a four-necked flask, pass nitrogen for 15 minutes, heat to 65°C, and add 5 / 6 of the aqueous solution of ammonium persulfate and sodium bisulfite in turn to initiate the reaction. After the temperature stabilizes at 80°C, slowly add 5g of ammonia water, control the addition for 15 minutes, and then keep warm for 2 hours. After the insulation is completed, add the remaining 1 / 6 of the aqueous solution of ammonium persulfate and sodium bisulfite, and continue the reaction for 0.5 hours. After the reaction is completed, cool to room temperature, add 25g of bisulfite compound to block the isocyanate crosslinker, stir evenly, filter the material, and obtain a printing adhesive with a silicone content of 10%.

[0092] Example 6

[0093] 245 g of deionized water, 10 g of an amphiphilic RAFT emulsifier represented by formula (1-1) and 8 g of N-n-butoxymethyl acrylamide were added to a reactor and stirred to form a water phase.

[0094] 103 g of butyl acrylate, 20.5 g of styrene, 20.5 g of acrylonitrile, 6 g of hydroxyethyl acrylate, 35 g of vinyl silicone oil (V401-1000) and 1 g of nano zinc oxide were added into a beaker and stirred evenly to prepare the oil phase.

[0095] Under the action of a high-speed shear emulsifier, the oil phase is slowly added to the water phase for pre-emulsification, and then ultrasonic dispersion is performed using an ultrasonic cell crusher, during which an ice bath is used for cooling to obtain an emulsion.

[0096] Dissolve 0.5g of ammonium persulfate and 0.5g of sodium bisulfite in 20g of deionized water respectively as initiators. Transfer the ultrasonically dispersed emulsion to a four-necked flask, pass nitrogen for 15 minutes, heat to 65°C, and add 5 / 6 of ammonium persulfate and sodium bisulfite aqueous solutions in sequence to initiate the reaction. After the temperature stabilizes at 80°C, slowly add 5g of ammonia water, control the addition for 15 minutes, and then keep warm for 2 hours. After the insulation is completed, add the remaining 1 / 6 of the ammonium persulfate and sodium bisulfite aqueous solutions and continue the reaction for 0.5 hours. After the reaction is completed, cool to room temperature, add 25g of bisulfite compound to block the isocyanate crosslinker, stir evenly, filter the material, and obtain a printing adhesive with a silicone content of 7%.

[0097] Example 7

[0098] 245 g of deionized water, 10 g of an amphiphilic RAFT emulsifier represented by formula (1-1) and 8 g of N-n-butoxymethyl acrylamide were added to a reactor and stirred to form a water phase.

[0099] 112 g of butyl acrylate, 16 g of styrene, 16 g of acrylonitrile, 6 g of hydroxyethyl acrylate, 35 g of vinyl silicone oil (V401-1000) and 1 g of nano zinc oxide were added into a beaker and stirred evenly to prepare the oil phase.

[0100] Under the action of a high-speed shear emulsifier, the oil phase is slowly added to the water phase for pre-emulsification, and then ultrasonic dispersion is performed using an ultrasonic cell crusher, during which an ice bath is used for cooling to obtain an emulsion.

[0101] Dissolve 0.5g of ammonium persulfate and 0.5g of sodium bisulfite in 20g of deionized water respectively as initiators. Transfer the ultrasonically dispersed emulsion to a four-necked flask, pass nitrogen for 15 minutes, heat to 65°C, and add 5 / 6 of ammonium persulfate and sodium bisulfite aqueous solutions in sequence to initiate the reaction. After the temperature stabilizes at 80°C, slowly add 5g of ammonia water, control the addition for 15 minutes, and then keep warm for 2 hours. After the insulation is completed, add the remaining 1 / 6 of the ammonium persulfate and sodium bisulfite aqueous solutions and continue the reaction for 0.5 hours. After the reaction is completed, cool to room temperature, add 25g of bisulfite compound to block the isocyanate crosslinker, stir evenly, filter the material, and obtain a printing adhesive with a silicone content of 7%.

[0102] Example 8

[0103]

[0104] 267 g of deionized water, 5 g of an amphiphilic RAFT emulsifier represented by formula (1-2) and 10 g of N-(isobutoxymethyl)acrylamide were added to a reactor and stirred to form a water phase.

[0105] 113 g of isooctyl acrylate, 15 g of styrene, 25 g of acrylonitrile, 5 g of hydroxypropyl methacrylate, 30 g of vinyl silicone oil (V401-1000) and 1.5 g of nano zinc oxide were added into a beaker and stirred evenly to prepare the oil phase.

[0106] Under the action of a high-speed shear emulsifier, the oil phase is slowly added to the water phase for pre-emulsification, and then ultrasonic dispersion is performed using an ultrasonic cell crusher, during which an ice bath is used for cooling to obtain an emulsion.

[0107] Dissolve 0.5g of potassium persulfate and 0.5g of sodium bisulfite in 20g of deionized water respectively as initiators. Transfer the ultrasonically dispersed emulsion to a four-necked flask, pass nitrogen for 15 minutes, heat to 65°C, and add 4 / 5 of potassium persulfate and sodium bisulfite aqueous solutions in sequence to initiate the reaction. After the temperature stabilizes at 80°C, slowly drop 2.5g of ammonia water, control the addition for 10 minutes, and then keep warm for 1.5 hours. After the insulation is completed, add the remaining 1 / 5 of the potassium persulfate and sodium bisulfite aqueous solutions and continue the reaction for 1 hour. After the reaction is completed, cool to room temperature, add 25g of alcohol compound to block the isocyanate crosslinker, stir evenly, filter the material, and obtain a printing adhesive with a silicone content of 6%.

[0108] Comparative Example 1

[0109] The difference between Comparative Example 1 and Example 2 is that no nano zinc oxide is added to the oil phase.

[0110] Comparative Example 2

[0111] The difference between Comparative Example 2 and Example 2 is that the emulsion after ultrasonic dispersion is directly reacted with all the initiators without adding ammonia water.

[0112] Comparative Example 3

[0113] The difference between Comparative Example 3 and Example 2 is that no vinyl silicone oil is added to the oil phase.

[0114] Comparative Example 4

[0115] 246 g of deionized water, 10 g of an amphiphilic RAFT emulsifier represented by formula (1-1) and 8 g of N-n-butoxymethyl acrylamide were added to a reactor and stirred to form a water phase.

[0116] 89.5 g of butyl acrylate, 13 g of styrene, 13 g of acrylonitrile, 6 g of hydroxyethyl acrylate, 62.5 g of vinyl silicone oil (V401-1000) and 1 g of nano zinc oxide were added into a beaker and stirred evenly to prepare the oil phase.

[0117] Under the action of a high-speed shear emulsifier, the oil phase is slowly added to the water phase for pre-emulsification, and then ultrasonic dispersion is performed using an ultrasonic cell crusher, during which an ice bath is used for cooling to obtain an emulsion.

[0118] Dissolve 0.5g of ammonium persulfate and 0.5g of sodium bisulfite in 20g of deionized water respectively as initiators. Transfer the ultrasonically dispersed emulsion to a four-necked flask, pass nitrogen for 15 minutes, heat to 65°C, and add 5 / 6 of ammonium persulfate and sodium bisulfite aqueous solutions in sequence to initiate the reaction. After the temperature stabilizes at 80°C, slowly add 5g of ammonia water, control the addition for 15 minutes, and then keep warm for 2 hours. After the insulation is completed, add the remaining 1 / 6 of the ammonium persulfate and sodium bisulfite aqueous solutions and continue the reaction for 0.5 hours. After the reaction is completed, cool to room temperature, add 25g of bisulfite compound to block the isocyanate crosslinker, stir evenly, filter the material, and obtain a printing adhesive with a silicone content of 12.5%.

[0119] The printing adhesives prepared in Examples 1-8 and Comparative Examples 1-4 and a commercial high-fastness adhesive (BASF TOW) were formulated into printing pastes. The coating used was coating black, and the coating dosage was 7%. After printing into printed fabric samples, dry and wet friction fastness, color depth and feel were tested. The test method is described as follows, and the test results are shown in Table 1.

[0120] Color depth: Use a spectrophotometer to measure the K / S value on the front of the printed fabric, where K is the colorant absorption coefficient and S is the colorant scattering coefficient. The larger the K / S value, the darker the color.

[0121] Table 1

[0122]

[0123] Note: The rubbing fastness is rated from 1 to 5, with 1 being the worst and 5 being the best.

[0124] Compared with commercial high-fastness adhesives on the market, the printing adhesive prepared by the present invention has better dry friction fastness, softer feel and deeper coloring. Comparative Examples 1-3, the results show that as the viscosity of the vinyl silicone oil increases, the molecular weight of the silicone oil increases, which can improve the dry friction fastness, soft feel and color depth of the adhesive. However, when the viscosity of the silicone oil is 2000, there is more slag in the polymerization process and the performance is significantly reduced. Therefore, the preferred viscosity of the vinyl silicone oil is 500-1000mPa·s. Comparative Examples 2, 4, and 5, it is found that the preferred addition amount of vinyl silicone oil is 6%-8%. Too high has no obvious effect on performance improvement and will cause the gel rate to increase. Comparative Examples 2, 6, and 7 verify the effect of the ratio of soft monomers to hard monomers on performance, and the preferred ratio is 3:1. According to Example 2 and Comparative Examples 1-2, it can be seen that the absence of zinc oxide or alkali aqueous solution will affect the polymerization stability, resulting in a high gel rate and reduced product performance. Comparative Example 3 shows that copolymerization of vinyl silicone oil can improve dry friction fastness and color depth. The transparency of the film formed by the adhesive in Comparative Example 4 is significantly reduced, which may be due to the excessively high content of organic silicon, resulting in phase separation, so the printing color depth is low.

[0125] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0126] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A method for preparing a printing adhesive, characterized in that: The steps include: Mixing an amphiphilic RAFT emulsifier, an aldehyde-free crosslinking monomer and water to prepare an aqueous phase, wherein the amphiphilic RAFT emulsifier has a molecular weight of 1000-5000; The oil phase is prepared by mixing acrylate, styrene, acrylonitrile, hydroxy acrylate, vinyl silicone oil and zinc oxide, wherein the mass fraction of the vinyl silicone oil in the oil phase is 10%-30%; The water phase and the oil phase are mixed for pre-emulsification, and then ultrasonically dispersed to obtain an emulsion; Under protective atmosphere and temperature conditions of 60°C-80°C, the emulsion is first reacted with part of the initiator, then an aqueous solution of alkali is added in batches for heat preservation, and finally the remaining initiator is added to continue the reaction. After the reaction is completed, a blocked isocyanate crosslinking agent is added and mixed to obtain a printing adhesive.

2. The method for preparing a printing adhesive according to claim 1, characterized in that: The general structural formula of the amphiphilic RAFT emulsifier is shown in formula (1), Among them, -R1 is selected from ethylmercapto, isopropylmercapto, butylmercapto or C12mercapto, -R2- is selected from the structural unit of styrene, the structural unit of acrylate, the structural unit of methacrylate or the structural unit of acrylonitrile, -R3- is selected from the structural unit of hydroxyethyl acrylate, the structural unit of hydroxyethyl methacrylate, the structural unit of hydroxypropyl acrylate or the structural unit of hydroxymethyl acrylamide, -R4- is selected from the structural unit of acrylic acid or the structural unit of methacrylic acid, -R5 is selected from isopropanoic acid, 2-diisobutyric acid, 2-isobutyronitrile, cyanopentanoic acid or 3-benzoic acid, the ratio of x to y is 1:2-1:9, and the ratio of the sum of x, y to n is 2:1-5:

1.

3. The method for preparing a printing adhesive according to claim 1, characterized in that: The dosage of the amphiphilic RAFT emulsifier is 0.1%-6% of the total mass of the aldehyde-free crosslinking monomer, acrylate, styrene, acrylonitrile, hydroxy acrylate and vinyl silicone oil.

4. The method for preparing a printing adhesive according to claim 1, characterized in that: The oil phase comprises 20-30 parts by weight of acrylate, 3-8 parts by weight of styrene, 3-8 parts by weight of acrylonitrile, 1-3 parts by weight of hydroxy acrylate, 2-10 parts by weight of vinyl silicone oil and 0.1-0.5 parts by weight of zinc oxide.

5. The method for preparing a printing adhesive according to claim 1, characterized in that: The aldehyde-free cross-linking monomer is selected from at least one of N-n-butoxymethyl acrylamide and N-(isobutoxymethyl) acrylamide; And / or, the acrylate is at least one selected from methyl acrylate, ethyl acrylate, butyl acrylate or isooctyl acrylate; And / or, the hydroxy acrylate is at least one selected from hydroxyethyl acrylate, hydroxypropyl acrylate, hydroxyethyl methacrylate or hydroxypropyl methacrylate; And / or, the vinyl silicone oil is selected from vinyl-terminated polydimethylsiloxane and vinyl-terminated polymethylvinylsiloxane, and the viscosity of the vinyl silicone oil is 300 mPa·s-2000 mPa·s.

6. The method for preparing a printing adhesive according to claim 1, characterized in that: In the emulsion, the mass ratio of the aldehyde-free cross-linking monomer to the acrylic ester is 1:4-1:

30.

7. The method for preparing a printing adhesive according to claim 1, characterized in that: The mass ratio of the partial initiator to the remaining initiator is 4:1-6:1; And / or, the total time of adding the aqueous solution of the alkali in batches is 10 min-15 min; And / or, the total amount of the initiator added is 0.05%-0.5% of the sum of the mass of the aldehyde-free crosslinking monomer, acrylate, styrene, acrylonitrile, hydroxy acrylate and vinyl silicone oil; And / or, the amount of the aqueous solution of alkali is 0.5%-6% of the sum of the mass of the aldehyde-free cross-linking monomer, acrylate, styrene, acrylonitrile, hydroxy acrylate and vinyl silicone oil; And / or, the amount of the blocked isocyanate crosslinking agent is 5%-15% of the sum of the mass of the formaldehyde-free crosslinking monomer, acrylate, styrene, acrylonitrile, hydroxy acrylate and vinyl silicone oil; And / or, the emulsion reacts with part of the initiator for 15 min-30 min, the aqueous solution of alkali is kept warm for 1.5 h-2 h, and the remaining initiator is added for 0.5 h-1 h.

8. The method for preparing a printing adhesive according to claim 1, characterized in that: The initiator is selected from at least one of ammonium persulfate, potassium persulfate or sodium bisulfite; And / or, the aqueous solution of alkali is at least one selected from an aqueous solution of potassium hydroxide, an aqueous solution of sodium hydroxide, and aqueous ammonia; And / or, the blocked isocyanate cross-linking agent is selected from at least one of bisulfite compound blocked polyisocyanate, alcohol compound blocked polyisocyanate or phenol compound blocked polyisocyanate.

9. A printing adhesive prepared by the method for preparing a printing adhesive according to any one of claims 1 to 8, characterized in that: The printing adhesive contains 2%-10% of organic silicon.

10. A printing adhesive as claimed in claim 9 for use in pigment printing.

Citation Information

Patent Citations

  • A soft, non-sticky, high-color-fastness pigment printing adhesive and its preparation method

    CN114163590B